2021
DOI: 10.1108/lht-06-2021-0179
|View full text |Cite
|
Sign up to set email alerts
|

Factors fostering the success of IoT services in academic libraries: a study built to enhance the library performance

Abstract: PurposeIn the modern era, libraries confront significant service challenges. Some challenges are linked to information resource management which includes direct availability of information for immediate decision making. The Internet of Things (IoT) is a recent technological shift that library personnel should be aware of because it has the potential to enhance information resource management. The purpose of the research is to highlight the willingness to adopt IoT technology in libraries.Design/methodology/app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 95 publications
(120 reference statements)
1
12
0
Order By: Relevance
“…The Internet of things (IoT) is now becoming ubiquitous (Sun et al , 2021; Chohan et al , 2021; Bokharaei Nia et al , 2021). Khan et al (2022) surveyed academic libraries in Nanjing, China. They noted that the IoT-augmented services in academic libraries should be supported through robust management practices and effective utilization of technological resources.…”
Section: Use Of Artificial Intelligence (Ai) Cloud Technology Interne...mentioning
confidence: 99%
“…The Internet of things (IoT) is now becoming ubiquitous (Sun et al , 2021; Chohan et al , 2021; Bokharaei Nia et al , 2021). Khan et al (2022) surveyed academic libraries in Nanjing, China. They noted that the IoT-augmented services in academic libraries should be supported through robust management practices and effective utilization of technological resources.…”
Section: Use Of Artificial Intelligence (Ai) Cloud Technology Interne...mentioning
confidence: 99%
“…The authors report the optimisation measures for the university library wayfinding signage system based on their findings. Besides signage, readers may also note that Internet of Things (IoT) technologies (Khan et al , 2021) are also useful for wayfinding, especially for people with impaired vision (Cheung et al , 2021).…”
Section: Wayfinding From the Users Perspective: The Connection Betwee...mentioning
confidence: 99%
“…The authors report the optimisation measures for the university library wayfinding signage system based on their findings. Besides signage, readers may also note that Internet of Things (IoT) technologies (Khan et al, 2021) are also useful for wayfinding, especially for people with impaired vision (Cheung et al, 2021).In a modern library, most services are provided through electronic systems. Therefore, understanding library users' need for these e-services is essential for academic librarians.…”
mentioning
confidence: 99%
“…Khan et al [52] In China examined the willingness to adopt IoT using DOI and TAM. The findings showed that relative advantage, compatibility, and trialability affected the perceived novel benefits and perceived performance.…”
Section: Combined Theoriesmentioning
confidence: 99%